Partisipasi Petani dalam Pengembangan Program Hutan Rakyat di Dusun Talang Gunung Desa Talang Batu Kecamatan Mesuji Timur Kabupaten Mesuji Provinsi Lampung - SUWARDANE, KOMANG EKE; SUARDI, I DEWA PUTU OKA; HANDAYANI, M. TH. (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.4, No.2, April 2015, 2016)
Abstract Farmer Participation in Developing Farm Forestry Program in Talang Gunung Backwoods Talang Batu Village East Mesuji Subdistrict Mesuji Regency Lampung Province The farm forestry is one of strategies which developed as the implementation from forestry paradigm development. Farm forestry has appeared as an alternative model for problem solving which caused by increasingly number of trees that lost from forests in the world and decreasing forest in developing countries . The purpose of this research is knowing about farmers’ participation in farm forestry program development in Talang Gunung Backwoods Talang Batu Village. This research has used qualitative descriptive analysis method. The variable in this research is participation. Based on the result of the research shows that farmers’ participation in farm forestry program development in Talang Gunung Backwoods Talang Batu Village was moderate with score achieving is 58, 97% from maximum score. This is caused by type of physical participation or nonphysical participation in some activities have only done by a few respondents. The advices which related to this research can be given by writer to farm forestrys sustainable in Talang Gunung Backwoods that is expected farmers to increase their participation in farm forestry development program in a physical participation and nonphysical participation. Keywords: Participation, Farmer, Farm Forestry.